The Fundamentals for Financing the Budgetary Institutions - Zakhidna Oksana R.; Spodaryk Tetiana I. (Bìznes Inform, 2019)
The proper construction of the financial system for providing the institutions in the budgetary sphere is an important factor in the formation and distribution of financial resources, facilitating the efficient performance of the State’s basic functions and tasks. The article is aimed at theoretical-analytical analyzing the problems of the current status of financing the budgetary institutions, defining the main problems present in the sphere of budgetary financing, as well as searching for not only optimal, but also efficient methods to address these problems. The article analyzes the problems arising in the financing of the budgetary institutions. Scientific approaches to understanding the essence of «budgetary institution» and «budgetary financing» are reflected. The main attributes, principles and forms of budgetary financing are defined. The volumes of budgetary financing are analyzed on the example of branches of the socio-cultural sector. It is proved that the problems that require further research are the poor status of financing, the lack of funds to upgrade the material-technical base, the lack of a stable and balanced legislation that would reliably and transparently regulate the economic activities of the budgetary institutions. Proposals are presented to improve the financing processes of budgetary institutions, which can be implemented by improving existing legislation in the sphere of budgetary financing and developing an effective control system, that would ensure the targeted inflow and rational use of funds directed to create an enabling environment for the financial security of their activities.